UTILIZING RECIPROCAL TEACHING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Saswandi, Tri (Menara Ilmu, 2018)
This research aimed to find out the extent to which Reciprocal Teaching Strategy can improve students’ reading comprehension and some factors which influence students’ improvement. This research used a Classroom Action Research by implementing two cycles which consisted of four stages (planning, action, observation, and reflection) in each cycle. The participants of this research were from the second year students of English Department of STKIP Muhammadiyah Sungai Penuh in academic year 2016/2017. The result showed that Reciprocal Teaching Strategy had improved students’ achievement in each cycle. It was found that in pre-test the students got 55 of mean score in getting main idea, 58 in detailed information, 60 in vocabulary and 54 in summary. The data showed that there were significant improvements in cycle II (mean score of main idea was 87, detailed information was 86, vocabulary was 96, and summary was 87). The factors that influenced students’ improvement are it encouraged students’ motivation, helps students in applying reading strategies, and assists students to do cooperative learning. Keywords: Reciprocal Teaching, Reading, Reading Comprehension